Optimalisasi Edukasi Lintas Sektor Berbasis Partisipasi Masyarakat sebagai Upaya Pencapaian SDGs Desa Watangsono Wonogiri - Muhammad Hilmy Pandoyo; Bilkis Sukreni Wulan Tunggal; Hasna Na’imah Setyawati; Nur Mahmud Fatturrahman; Anandita Salma Larasati; Ben Citra Putri Essla; Karis Cindiana; Maulida Alfi Sa’adah; Nur Hidayah; Rahma Azra Calista; Diana Tantri Cahyaningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the implementation of cross-sector education based on community participation as an effort to achieve the Sustainable Development Goals (SDGs) in Watangsono Village, Wonogiri. This research employed a descriptive qualitative approach by collecting data through participatory observation, documentation, and Focus Group Discussions (FGD) involving key stakeholders in the village. The results show that the implementation of cross-sector educational programs covering education, health, economy, and environment has a significant impact on improving community knowledge, skills, and awareness. Community participation was reflected through active involvement in various practical activities, such as anti-bullying education, digital literacy training, stunting prevention through local food processing, herbal plant utilization, natural pesticide production, family health massage practices, and strengthening local economic capacity. The participatory and applicative approach encourages two-way knowledge transfer and strengthens community capacity in managing local resources sustainably. Despite challenges such as limited resources and time constraints, the program demonstrates positive contributions to supporting SDGs achievement at the village level. Therefore, cross-sector education based on community participation can serve as an effective strategy in empowering rural communities and fostering sustainable development.